Advances in Precise Structure Control and Assembly toward the Carbon Nanotube Industry (Adv. Funct. Mater. 11/2022). (8th March 2022) - Zhu, Zhenxing; Cui, Chaojie; Bai, Yunxiang; Gao, Jun; Jiang, Yaxin; Li, Bofan; Wang, Yao; Zhang, Qiang; Qian, Weizhong; Wei, Fei
Abstract : Controlled Synthesis The commercialization of carbon nanotubes (CNTs) depends on rapid development in precise structure control and morphological assembly technology. In article number 2109401, Weizhong Qian, Fei Wei, and co‐workers summarize the catalytic growth mechanism of defect‐free CNTs. The template‐assisted morphological assembly is subsequently introduced as an efficient route towards their mass production. Finally, more cutting‐edge applications are presented with potential breakthroughs in fibers, energy, and electronics.